3D non-linear behavior of masonry arch bridges - Milani, G. (2012)
In this paper, the static non-linear behavior of masonry bridges is numerically analyzed by means of a 3D FE numerical code. In particular, the three dimensional behavior of the structures when subjected to eccentric loads, the actual 3D geometry of the bridges (particularly important when skew arches are analyzed) and the strengthening effect induced by the backfill are considered. The code is non-commercial and is applied here for the first time in presence of a very large number of elements and different materials. It relies in a FE discretization of the structure by means of rigid infinitely resistant eight-noded parallelepiped elements and non-linear interfaces, exhibiting deterioration of the mechanical properties. Each material of the bridge (arch, buttresses, piers, and fill) is suitably modeled using interfaces having different constitutive behavior and mechanical properties. Two real scale masonry bridges are analyzed, namely a skew single span structure experimentally tested up to failure at the Bolton Institute, UK and a straight multi span bridge constituted by five circular arches and loaded with an eccentric load. Both 2D and 3D limit analyses are also performed to have full insight into the actual capabilities of the 3D approach to reproduce peak loads and deformed shapes at failure and, at the same time, to investigate limitations of 2D hypotheses when transversal effects induced by geometry and load eccentricity are not considered.